BACK MATTER (Publication Ethics, Author Index, Subject Index, Author Biography, Acknowledgment, Template, Author Guidelines) - - - (Program Studi Pendidikan Matematika Program Pascasarjan Universitas Negeri Yogyakarta, 2016)
-